Alcohol Inhibits NR2B-Containing NMDA Receptors in the Ventral Bed Nucleus of the Stria Terminalis - Kash, Thomas L (2007)
Components of the mesolimbic dopamine system, in particular dopaminergic cells in the ventral tegmental area (VTA), have been implicated in the acute reinforcing actions of ethanol. The ventral bed nucleus of the stria terminalis (vBNST) potently regulates dopaminergic cell firing in the VTA, and has been implicated in the behavioral actions of ethanol. The N-methyl-D-asparate receptor (NMDAR) is a major molecular target of ethanol, however, current evidence suggests that ethanol regulation of NMDAR function is widely variable and likely depends on a number of factors. Thus, it is critical to investigate ethanol regulation of NMDAR function at synapses relevant to ethanol-regulated behaviors, such as in the vBNST. Here we show, using multiple techniques, that ethanol inhibits NMDAR function in vBNST neurons in a postsynaptic fashion. Further, we demonstrate the functional presence of both NR2A and NR2B-containing NMDARs in the vBNST. While genetic removal of NR2A did not alter the magnitude of ethanol inhibition, pharmacological blockade of NR2B rendered synaptically activated NMDARs insensitive to ethanol inhibition. Finally, we demonstrate that ethanol inhibits NMDARs in cells in the vBNST that project to the VTA, providing a direct means by which ethanol in the vBNST can modulate the dopaminergic system.